One Step Rapid Sensitive Method for the Diagnosis of Hemolysin Gene of Aeromonas hydrophila by Polymerase Chain Reaction - Hota Sankirtha; Sugumar Vimal; Alex Arockia; Brahma Neha; Navya Kotra (Wolters Kluwer Medknow Publications, 2024)
Aeromonas hydrophila is a Gram-negative bacterium that has been linked to serious illnesses in both humans and animals. The presence of hemolysin, a virulence factor, is critical in the development of A. hydrophila-related illnesses. As a result, precise and timely detection of the hemolysin gene is critical for efficient diagnosis and prevention of many illnesses. The PCR is used in this study to detect the hemolysin gene of A. hydrophila in a novel, fast, and highly sensitive one-step technique. Specific primers were constructed to amplify a conserved area within the hemolysin gene to achieve both specificity as well as sensitivity. The PCR assay was rigorously optimized, taking temperature, primer concentration, and reaction time into account, in order to maximize the efficiency and reliability of this method. In conclusion, this method's simplicity, sensitivity, and specificity make it highly promising for regular diagnostic applications. Its application would allow for the early detection of A. hydrophila infections, allowing for more effective treatment and control methods.